Local Surface Chemistry Dynamically Monitored by Quantitative Phase Microscopy. Issue 1 (17th November 2021) - Brasiliense, Vitor; Audibert, Jean‐Frédéric; Wu, Tengfei; Tessier, Gilles; Berto, Pascal; Miomandre, Fabien
Abstract: Surface modification by photo grafting constitutes an interesting strategy to prepare functional surfaces. Precision applications, however, demand quantitative methods able to monitor and control the amount and distribution of surface modifications, which is hard to achieve, particularly in operando conditions. In this paper, a label‐free, cost‐effective, all‐optical method based on wavefront sensing which is able to quantitatively track the evolution of grafted layers in real‐time, is presented. By positioning a simple thin diffuser in the close vicinity of a camera, the thickness of grafted patterns is directly evaluated with sub‐nanometric sensitivity and diffraction‐limited lateral resolution. By performing an in‐depth kinetic analysis of the local modification of an inert substrate (glass cover slips) through photografting of arydiazonium salts, different growth regimes are characterized and several parameters are estimated, such as the grafting efficiency, density and the apparent refractive index distribution of the resulting grafted layers. Both focused and widefield‐grafting can be quantitatively monitored in real time, providing valuable guidelines to maximize functionalization efficiency. The association of a well‐characterized versatile photografting reaction with the proposed flexible and sensitive monitoring strategy enables functional surfaces to be prepared, and puts surface micro‐ to submicro‐structuration within the reach of most laboratories. Abstract : Herein, diffuser‐based phase sensing and imaging, a quantitative phase imaging method for monitoring the advancement of surface modification reactions with sub‐nanometric to nanometric precision is introduced. Its capacity to analyze grafting reactions is illustrated by performing and in‐depth analysis of the photografting of aryldiazonium salts onto glass, revealing grafting regimes and extracting elusive physical and chemical parameters.